2017
DOI: 10.3928/01477447-20161202-04
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ankle Arthrodesis for Severely Comminuted Tibial Pilon Fractures

Abstract: Management of severely comminuted, complete articular tibial pilon fractures (Rüedi and Allgöwer type III) remains a challenge, with few treatment options providing good clinical outcomes. Twenty patients with severely comminuted tibial pilon fractures underwent primary ankle arthrodesis with a retrograde calcaneal nail and autogenous fibular bone graft. The fusion rate was 100% and the varus malunion rate was 10%. Fracture union occurred at a mean of 16 weeks (range, 13-18 weeks) postoperatively. Primary ankl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
(15 reference statements)
0
14
1
Order By: Relevance
“…AOFAS scores was reported in only one other study [39]. Our average value of 53.0 is lower than their value of 85.4.…”
Section: Proms and Bone Unioncontrasting
confidence: 85%
See 2 more Smart Citations
“…AOFAS scores was reported in only one other study [39]. Our average value of 53.0 is lower than their value of 85.4.…”
Section: Proms and Bone Unioncontrasting
confidence: 85%
“…Reason could be twofold. We reported AOFAS scores at 6 months post-injury, but Al-Ashhab et al reported it at final follow-up [39]. Also, 45% of our patients had open fractures, whereas their cohort had no open fractures [39].…”
Section: Proms and Bone Unionmentioning
confidence: 55%
See 1 more Smart Citation
“…Other indications include arthrosis from previous infection, talar avascular necrosis, 59 neuropathy, inflammatory arthropathy 121 including hemophilia, 11 salvage of failed arthroplasty, 57 and rarely primary treatment following severe ankle trauma. 2,112 Many techniques have been described for ankle fusion, and they broadly fall into 2 categories: open arthrotomy and minimally invasive. One major concern of arthrodesis is the acceleration of adjacent joint arthritis, which has been shown to be present in the triple joint complex, naviculocuneiform, tarsometatarsal, and first metatarsophalangeal joints after ipsilateral ankle fusion at 22-year follow-up.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…3,9,17,28 Described methods for ankle arthrodesis include tibiotalocalcaneal (TTC) hindfoot nails, ringed external fixators, and tibiotalar arthrodesis with crossed screws or plating. Although primary arthrodesis has been described for the management of severe pilon fractures, 1,14 there is a paucity of literature describing its role in acute diabetic ankle fractures without concomitant Charcot arthropathy. Here, we present a case series of 13 diabetic ankle fractures that underwent primary arthrodesis following an ankle fracture with a focus on patient and injury characteristics and operative outcomes/complications.…”
Section: Introductionmentioning
confidence: 99%